An assessment of the impact of customs union on Turkish bilateral trade flows with the EU: a gravity model approach - Bebek, Ufuk Güneş (My University, 2006)
Literatürde Gümrük Birliği’nin Türkiye üzerindeki etkilerini tartışan pek çok çalışma bulunmaktadır. Gümrük Birliği antlaşması ile birlikte Türkiye’nin dış ticaret açığının arttığı gözlemlenmiştir. Türkiye ile Avrupa Birliği arasındaki ticaret hacmi değişimleri ile ilgili pek çok görüş öne sürülürken, Gümrük Birliği’nin etkileri üzerinde yapılmış yeterli ampirik çalışma bulunmamaktadır. Bu çalışma, Gümrük Birliği’nin Türkiye’nin Avrupa Birliği ile ticaret akışının üzerindeki etkilerini iki farklı gravity model spesifikasyonu kullanarak panel data analizi çerçevesinde incelemektedir. Toplam ticaret hacmindeki artışa rağmen, Gümrük Birliği antlaşmasının artan dış ticaret açığının bir sebebi olup olmadığının açıkça görülmesi için, ithalat ve ihracat rakamları için ayrı analizler yapılmıştır. Her iki spesifikasyona ait regresyon sonuçları, Gümrük Birliği Antlaşması’nın Türkiye’nin ithalatını anlamlı bir şekilde arttırmasına rağmen, Türkiye’nin ihracatı üzerinde anlamlı bir etkiye sahip olmadığını göstermektedir. Bu çalışmanın ampirik sonuçları, Gümrük Birliği Antlaşmasının artan dış ticaret açığının sebeplerinden biri olduğunu işaret etmektedir.

There have been numerous studies discussing the advantages and disadvantages of a Customs Union with Turkey. With the establishment of the Customs Union agreement, Turkey’s trade deficit increased through the consequent years. However there hasn’t been sufficient empirical analysis on the effects of the Customs Union, but mainly discussions focusing on changes in the volume of bilateral trade between Turkey and the EU. This study attempts to analyze the impact of the Customs Union on Turkey’s trade flows with the EU using two different specifications of the gravity model in a panel data framework. Although the total volume of trade has increased, this study will investigate the imports and exports separately to find whether the Customs Union agreement is really a cause for the increasing trade deficit or not. The regression results for both specifications suggest that although the Customs Union significantly increased the volume of Turkey’s imports, this agreement’s effect on the exports of Turkey is insignificant. The study’s empirical findings suggest that the Customs Union agreement is one of the causes of the increasing trade deficit.
Keywords: Avrupa Birliği_Gümrük Birliği_Türkiye; Ekonomi; Gümrük Birliği_Türkiye; Türkiye_Dış Ticaret